Adamantinoma-Like Ewing’s Family Tumor of the Sino Nasal Region: A Case Report and a Brief Review of Literature - Pushpa Mahadevan; Subramaniam Ramkumar; V. P. Gangadharan (Case Reports in Pathology)
Ewing's sarcoma family of tumors (EFTs) are malignant mesenchymal tumors with a predilection for bone and soft tissue. They are characterized by their monomorphic small blue round cell morphology. However rare morphologic variants of EFTs can also show overt epithelial differentiation in the form of squamoid differentiation along with strong cytokeratin expression. This particular subset of EFTs are known as adamantinoma-like EFTs which can be difficult to differentiate from epithelial head and neck malignancies. Here we report a case of sinonasal adamantinoma-like EFT in an 18-year-old male patient. The lesion differed from a typical EFT by means of overt squamoid differentiation which showed a basaloid appearance with peripheral palisading. The immunohistochemistry was positive for pan-cytokeratin, p40, p63, ERG, FLI1, and CK5/6. It was negative for actin, desmin, and WT-1. Initial diagnosis of a basaloid squamous cell carcinoma was made. Further molecular studies were also done due to the complex presentation of the tumor. EWSR testing with break-apart analysis confirmed EWSR1 and FLI1 rearrangements. Further confirmation was done with RT-PCR. The case was found to be positive for EWS-FLI-1 translocation. The revised immunohistochemistry panel showed CD99, ERG, FLI1, and synaptophysin positivity. The lesion was reclassified as an adamantinoma-like ES. Our case reinforces the fact that a subset of EFTs can show histomorphologic and immunohistochemical features of aberrant epithelial differentiation. These cases are difficult to differentiate from usual epithelial malignancies which occur in this region. This diagnostic pitfall can be avoided by the inclusion of CD99 and/or FLI1 in the immunohistochemical assessment of any round cell malignancy at any anatomic location. A strong and diffuse CD99 positivity should prompt molecular testing for the presence of EWSR1 gene rearrangements.